2012
DOI: 10.1039/c1cs15239d
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides as building blocks for nanotherapeutics

Abstract: The use of polysaccharides as building blocks in the development of nano-sized drug delivery systems is rapidly growing. This can be attributed to the outstanding virtues of polysaccharides such as biocompatibility, biodegradability, low toxicity and low cost. In addition, the variety of physicochemical properties and the ease of chemical modifications enable the preparation of a wide array of nanoparticles. This tutorial review describes the properties of common polysaccharides, the main mechanisms for polysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
284
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(286 citation statements)
references
References 74 publications
2
284
0
Order By: Relevance
“…Another of those molecules is pullulan, a neutral polymer consisting of α-(1,6)-linked maltotriose residues, which in turn are composed of three glucose molecules connected to each other by an α-(1,4) glycosidic bond (Chiellini et al, 2008;Mizrahy and Peer, 2012;Namazi et al, 2011). Pullulan is produced from starch by the fungus Aureobasidium pullulans and evidences water solubility (Leathers, 2003;Rekha and Chandra, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another of those molecules is pullulan, a neutral polymer consisting of α-(1,6)-linked maltotriose residues, which in turn are composed of three glucose molecules connected to each other by an α-(1,4) glycosidic bond (Chiellini et al, 2008;Mizrahy and Peer, 2012;Namazi et al, 2011). Pullulan is produced from starch by the fungus Aureobasidium pullulans and evidences water solubility (Leathers, 2003;Rekha and Chandra, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the most frequently explored polysaccharide for the design of nanodelivery systems was chitosan, a cationic polymer composed of repeating β-(1,4)-linked N-acetylglucosamine and D-glucosamine units, which is obtained by chitin deacetylation and assumes different molecular weights and deacetylation degrees (Chiellini et al, 2008;Hassani et al, 2012;Mizrahy and Peer, 2012). Apart from the reported biocompatibility and biodegradability (Dornish et al, 1997;Grenha et al, 2010a;Hirano et al, 1988), the most outstanding properties of chitosan rely on its mucoadhesive character (Lehr et al, 1992) and demonstrated ability to potentiate transmucosal absorption both as molecule (Artursson et al, 1994;Borchard et al, 1996;Portero et al, 2002) and in the form of nanoparticle (Al-Qadi et al, 2012;De Campos et al, 2001;Fernández-Urrusuno et al, 1999a;Prego et al, 2005a;Yamamoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, HA, a natural polysaccharide that has been demonstrated as one of the most promising biomaterials,10 was utilized to encapsulate DOX and CDDP via electrostatic and chelate interactions with its side carboxyl groups, respectively ( Scheme 1 ). The number‐average molecular weight ( M n ) and polydispersity indices (PDI) of HA determined by gel permeation chromatography (GPC) was 16 060 g mol −1 and 1.7, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Chemically, this polymer consists of a-(1,6)-linked maltotriose residues, which in turn are composed of three glucose molecules connected to each other by a-(1,4) glycosidic bonds [6,7]. Several properties have been reported for this material that make it attractive for drug-delivery purposes, including its adhesive ability, as well as the capacity to form fibers and thin biodegradable films [7].…”
Section: Editorialmentioning
confidence: 99%